Study of Video Annotations In External Practices Of University Learning - Cebrián-Robles, Daniel; Cebrián-de-la-Serna, Manuel; Monedero-Moya, Juan José (My University, 2015)
The digital video as code and learning technology has extensive scientific literature (Bartolome, 1997; Aguaded and Sánchez, 2008). However, the increase of digital video services on the Internet has facilitated and increased the use of video for education. With a recent important increase of videos as contained in the MOOC (Massive Open Online Course). This context has also created the expansion of educational practices based on models for collaborative learning and mediated by technology (Computer Supported Learning collaborative -CSCL-). The study of these practices is proving to be effective for teachers in service and initial training practices if it is analyzed collectively (Hosack, Br tools, 2010;. Picci, Calvani, & Bonaiuti, 2012; Etscheidt & Curran, 2012; Ingram , 2014). There is interest in literature reviews on the reflective capabilities with the use of video for initial teacher training (Orland-Barak & Rachamim, 2009; Rich and Hannafin 2009; Rich & Trip, 2011) to which we expand in (Wallet, Cebrian & Desenne, 2015). This work is part of a research project in progress [1] which aims to implement a federated portfolio model of multimedia evidences. This model uses a digital portfolio (from now on we will call ePortfolios) with three different federated tools (1. Digital rubric or eRubric, 2. Webquest and 3. Open Video Annotations -Ova-) created by our research and development group Gtea [2 ]. The OVA tool was created within the MOOC of edX in collaboration with Harvard University in 2013 [3]. So it, we need to create another standalone tool to design their own interface to use this tool in this project. This design was evaluated through user usability and satisfaction (Monedero, Cebrian & Desenne, 2015). This study focuses on the ease and functionality of the OVA tool so that students to collect evidence on their digital multimedia portfolios. Especially, analyzes the competences that students show when annotate video in order to explain their learning experiences and respond to the skills that are required in the eRubrics in different teaching contexts (external and laboratory practices).
Keywords: Enseñanza superior - Innovaciones tecnológicas; Video Annotations; Multimedia annotations; Educational software; EPortfolios; University education